Non-literal Meaning Analysis in the Novel "On the Bright Side, I'm Now the Girlfriend of a Sex God" - Raden Arief Nugroho (ELITE JOURNAL, 2020)
Since meaning is categorized into literal and non-literal ones, semantics scholars have been agreeing that the focus of language research should be more of the non-literal ones. Non-literal meaning analysis is pivotal since the meaning cannot be interpreted literally. This study concerns about the analysis of non-literal meaning consisting of metaphors, connotative meaning, idioms, and figurative meaning in the novel “On the Bright Side, I’m now the Girlfriend of a Sex God”. Using a library research under the umbrella of descriptive qualitative research paradigm, the researcher sampled 60 pages of the novel. The sample calculation itself was in accordance with Wilumila’s proposition of systematic sampling (2002:7). The discussion suggests that non-literal meaning found in the novel is used to hide speakers’ innuendos behind the curtain, for example the humor element contained in the novel can be revealed without showing the intention to joke. Thus, it can be concluded that the use of non-literal meaning in the novel simply serves as hyperbolic and poetic functions.